Using Mobile Technology to Promote Higher-Order Thinking Skills in Elementary Mathematics - Versoza, Debbie Marie (Archīum Ateneo, 2021)
The problem of rote-based learning in mathematics is well documented. Mobile technology can provide a potential solution; especially when application (app) design is based on sound pedagogical principles and gamification elements. However; an inventory of available mobile apps for mathematics reveals that many of the available apps are guided by a behaviorist perspective that favors repetition over meaningful learning. This paper reports on the design of mobile mathematics apps that harness gamification techniques to promote higher-order thinking skills (HOTS) even in basic elementary school concepts such as number comparison; and addition and subtraction. The integration of these apps in the classroom is also discussed.